2014
DOI: 10.5455/ajvs.166197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sesame Oil on Serum and Liver Lipid Profile in Hyperlipidemic Rats.

Abstract: This study was conducted to investigate the effect of sesame oil on serum and hepatic lipid profile in induced hyperlipidemic rat .Eight forty rats were randomly divided into equal six groups of eight animals each for 30 days as follows : The first group(control) was kept on basal diet and water, the second group was kept on basal diet added to it sesame oil (SSO)5%, the third group was given a basal diet supplemented by SSO10%,the fourth group (hyperlipidemic) ,hyperlipidemia was induced at last two weeks by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
4
11
0
2
Order By: Relevance
“…Concerning the effects of (SO) on TL, TC and TG, our results are at the same line with (Taha et al, 2014) who reported that, treatment of hyperlipidimic rats with (SO) 5&10% showed hypolipidimic activity as they decreased hepatic level of TG & TC. Concerning sage effects on plasma lipids (Eidi and Eidi., 2009) reported that, sage ethanolic extract significantly decreased serum glucose, triglycerides and total cholesterol.…”
Section: Effects Of Sage Sesame and Olive Oils On Total Lipids Cholesterol And Triglycerides In Nonalcoholic Fatty Liver Ratssupporting
confidence: 92%
“…Concerning the effects of (SO) on TL, TC and TG, our results are at the same line with (Taha et al, 2014) who reported that, treatment of hyperlipidimic rats with (SO) 5&10% showed hypolipidimic activity as they decreased hepatic level of TG & TC. Concerning sage effects on plasma lipids (Eidi and Eidi., 2009) reported that, sage ethanolic extract significantly decreased serum glucose, triglycerides and total cholesterol.…”
Section: Effects Of Sage Sesame and Olive Oils On Total Lipids Cholesterol And Triglycerides In Nonalcoholic Fatty Liver Ratssupporting
confidence: 92%
“…Our results are at a harmony with (Taha et al, 2014)who reported that supplementation with (SO) possess a better improving potential for hyperlipidemia, serum glucose, adiponectin, thyroid hormones, hepatic lipid profile. Concerning sage effect on blood glucose level (Eidi et al, 2005)suggested that aqueous extract of sage has been found to exhibit insulinlike activities.…”
Section: Effects Of Sage Sesame and Olive Oils Alone Or In Combination On Serum Leptin Hormone And Blood Glucose Levels In Obese Nonalcohsupporting
confidence: 90%
“…Moreover, there were no significant changes were observed among the treated groups. So that ginger or cinnamon with Halawa tahinia have no side effects on liver functions Sesame oil at 5% was possess a better improving potential for hyperlipidemia, serum glucose, thyroid hormones and hepatic lipid profile than sesame oil at 10% [85].…”
Section: Resultsmentioning
confidence: 97%